Implementasi Terapi Pijat Oksitosin dengan Pemberdayaan Kader pada Ibu Post Partum - Lutfiana Puspita Sari; Lusinta Agustina (Poltekkes Kemenkes Surakarta, 2020)
Background: Efforts to help the success of government programs related to exclusive breastfeeding must be done as early as possible from 36 weeks of gestation. Massage done in the area around the spine in pregnant women will help the secretion of the hormones oxytocin and prolactin. The oxytocin released after the massage process will stimulate labor contractions and prepare for the breastfeeding process, so it is hoped that regular stimuli given in the form of oxytocin massage will affect the production of milk produced. So it is important to introduce oxytocin massage from an early age to cadres, pregnant women, and nursing mothers. Through cadres, pregnant and lactating mothers will always be reminded to prepare for milk production from pregnancy. The purpose of this activity are to optimize the production of breastmilk in post partum mothers through mentoring health cadres. Methods: Method this study is used oxytocin massage intervention and health education. Results: Of this activity are health education and oxytocin massage intervention can increase knowledge cadre skills to help post partum mothers succeed in exclusive breastfeeding. Conclusion: Oxytocin massage can be an intervention alternative to optimize the production of breastmilk in post partum mothers.